Exploring the Role of Governance in Corporate Social Responsibility: Impact on Performance and Sustainable Practices - Gaffar, Ummu Habibah; Susanti, Gita; Alwi, ‎ (KnE Social Sciences, 2025)
This research explores the determinants of corporate social rsesponsibility (CSR) governance and its impact on economic and social performance, with a focus on sustainable CSR practices. The study employs a systematic literature review (SLR) methodology to synthesize existing research on CSR, governance, and its outcomes. The problem statement addresses the need for a comprehensive understanding of the factors influencing CSR, particularly focusing on corporate governance mechanisms, government regulations, and external pressures from stakeholders. This research aims to analyze how CSR practices are managed and implemented across various industries and countries, with an emphasis on achieving sustainable, social, and environmental outcomes. The methodology involves analyzing qualitative data based on the meta-analyses from peer-reviewed journals. Key theories guiding this study include legitimacy theory, which explains companies’ motivation to engage in CSR to gain social legitimacy. This approach highlights the importance of transparency, accountability, and aligning CSR practices with social expectations. The findings reveal that good corporate governance, including board independence and gender diversity, positively influences CSR effectiveness. Government intervention through strict regulations and fiscal incentives also plays a critical role in ensuring the successful implementation of CSR policies. However, challenges such as greenwashing and the gap between developed and developing countries remain, requiring a more systematic evidence-based approach to CSR evaluation. The study concludes that effective CSR requires collaboration between the private sector, government, and civil society to create a transparent and accountable system for long-term sustainability.